Separation of Membrane Vesicles and Cytosol from Yeast, Cultured Cells, and Bacteria in a Small Volume Self-Generated Gradient in a Fixed-Angle Rotor - John Graham (The Scientific World Journal)
There are many situations when it is necessary to separate rapidly and efficiently a cytosolic and a membrane vesicle fraction from yeast, cultured cells, or from bacteria. This Protocol Article describes the flotation of the vesicles through a self-generated gradient from a dense sample zone using the low-viscosity medium iodixanol. As the sample is exposed to the gmax the tendency of the proteins to sediment overcomes any diffusion in the opposite direction and are therefore completely separated from the vesicles.